2015
DOI: 10.1080/19443994.2014.942559
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of removal of pharmaceuticals and personal care products by nanofiltration membranes

Abstract: A B S T R A C TMuch attention has been paid to pharmaceuticals and personal care products (PPCPs). Nanofiltration (NF) is a new type of separation technology developed between ultrafiltration and reverse osmosis (RO) in the mid-1980s, which is a continuation and development branch of the ultra-low pressure RO technology. PPCPs are a kind of water ubiquitous trace organics, and there are some disadvantages of the PPCPs, such as recalcitrance, accumulation of biological toxicity and long-term dangers, which grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Thereby, the pH value of the solution plays a significant role in removing charged drugs by NF. Some studies have reported that the role of electrostatic repulsion is very crucial in removing the charged organic solutes [20][21][22][27][28][29]. Based on our literature survey, the role of steric exclusion for removal the charged organic solutes is still not clear.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Thereby, the pH value of the solution plays a significant role in removing charged drugs by NF. Some studies have reported that the role of electrostatic repulsion is very crucial in removing the charged organic solutes [20][21][22][27][28][29]. Based on our literature survey, the role of steric exclusion for removal the charged organic solutes is still not clear.…”
Section: Introductionmentioning
confidence: 84%
“…Recently, some researchers investigated the removal performance of drugs by NF technology [20][21][22][23][24][25]. Three major drug removal mechanisms are proposed, including steric exclusion, electrostatic repulsion and adsorption.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As an alternative technology, the use of membranes has attracted attention due to its wide range of removal, low energy consumption, compact equipment, and simple operation [ 12 , 13 ]. One of the membrane separation processes, nanofiltration (NF) is a good means of removing PPCPs [ 14 , 15 ]. However, in practical applications, the traditional NF membrane does not simultaneously provide good chemical stability, microbial resistance, and high mechanical strength.…”
Section: Introductionmentioning
confidence: 99%